What gastroenterologists should know about direct oral anticoagulants. Issue 10 (October 2020) - Radaelli, F.; Fuccio, L.; Paggi, S.; Bono, C. Del; Dumonceau, J.M.; Dentali, F.
Abstract: Direct oral anticoagulants are being increasingly used in patients with non-valvular atrial fibrillation and venous thromboembolism, due to their improved efficacy/ safety ratio, a predictable anticoagulant effect without need for routine coagulation monitoring, and fewer food and drug interactions compared with vitamin K antagonists. Gastrointestinal bleeding remains a serious complication, whose management is challenging for gastroenterologists due to the lack of a standardized clinical approach. Clinical experience on periendoscopic management of these drugs is still limited and there is a paucity of clinical data supporting guidelines recommendations', and this ultimately turns out in different, unsubstantiated and potentially harmful practices of patient management. Present study will provide a thorough revision on the risk of GI bleeding for DOAC therapy and the identification of patient risk factors to individualize treatment. Moreover, the approach to management of DOACs in case of bleeding complications is discussed, and an algorithm of different strategies in presence or not of plasma level measurement is proposed. Finally the periendoscopic management for elective procedures will be reviewed, at the light of the guideline recommendations and new evidences from observational studies.